"We Still Have a Long Way to Go": How State Education Leaders' Understanding and Engagement Shapes English Learner Identification of Indigenous Students - Ilana M. Umansky; Taiyo Itoh (SAGE Publishing, 2024)
Federal law defines English learner (EL) eligibility differently for Indigenous, compared to non-Indigenous, students, allowing for broader entry into the EL category, along with its accompanying resources and services. We interviewed EL leaders from 25 state departments of education to learn about their level of understanding of the differentiated definition and their work to interpret and implement it. Drawing upon and expanding recent conceptual frameworks, we explored how EL leaders' knowledge about and engagement with EL constituents influence their ability to interpret and implement policy in equity-expansive ways. We found that many EL leaders had little understanding of the federal law and weak engagement with Indigenous Tribes and communities, both of which limited their work. In states where leaders had deeper knowledge and engagement, they were more actively interpreting and implementing federal law, particularly with the aim of increasing Indigenous EL-classified students' access to heritage language and culturally-sustaining programs.